THE IMPORTANCE OF THE PHARMACIST IN PROMOTING THE RATIONAL USE OF MEDICINES (CIPEEX, 2025)
The irrational use of antibiotics represents a critical challenge for public health, as it promotes bacterial resistance, reduces therapeutic efficacy, and increases healthcare costs. Self-medication is identified as one of the main contributing factors, which can lead to adverse effects such as allergies, gastrointestinal disorders, and intoxications. This study aimed to analyze the impacts of inappropriate antibiotic use and to highlight the pharmacist’s role in promoting the rational use of medicines. The methodology consisted of a bibliographic review of publications from 2020 to 2024, retrieved from databases such as Google Scholar, SciELO, PubMed, and BDTD. The results demonstrate that pharmacists play a key role in patient counseling, prescription assessment, dispensing control, identification of drug interactions, and participation in hospital infection control committees. Additionally, the study addresses ozone therapy as a complementary practice, emphasizing its historical background, therapeutic applications, benefits, risks, and the professional regulation established by the Federal Council of Pharmacy. It is concluded that the pharmacist’s role, both in ensuring the rational use of antibiotics and in the safe application of ozone therapy, is fundamental for patient safety and treatment effectiveness.
Keywords: Pharmacist; Ozone therapy; Bacterial resistance; Rational use of medicines